Differences between primary care physicians and specialised neurotologists in the diagnosis of dizziness and vertigo in Japan. Issue 9 (17th September 2020) - Ito, T; Matsuyama, S; Shiozaki, T; Nishikawa, D; Akioka, H; Yamanaka, T; Kitahara, T
Abstract: Objective: Vertigo and dizziness are frequent symptoms in patients at out-patient services. An accurate diagnosis for vertigo or dizziness is essential for symptom relief; however, it is often challenging. This study aimed to identify differences in diagnoses between primary-care physicians and specialised neurotologists. Method: In total, 217 patients were enrolled. To compare diagnoses, data was collected from the reference letters of primary-care physicians, medical questionnaires completed by patients and medical records. Results: In total, 62.2 per cent and 29.5 per cent of the patients were referred by otorhinolaryngologists and internists, respectively. The cause of vertigo or dizziness and diagnosis was missing in 47.0 per cent of the reference letters. In addition, 67.3 per cent of the diagnoses by previous physicians differed from those reported by specialised neurotologists. Conclusion: To ensure patient satisfaction and high quality of life, an accurate diagnosis for vertigo or dizziness is required; therefore, methods or materials to improve the diagnostic accuracy are needed.